Moral Geographies of Re-Existence - Projects of the Cluster (Presenting The Cluster Projects, 2022)
Our research project sheds light on the ways in which Afro-descendant communities resist and re-exist in postcolonial and post-slavery Latin America. We focus on Salvador da Bahia (Brazil) and Cartagena de Indias (Colombia), two major arrival ports of the transatlantic slave trade. These traumatic places of enslavement and colonization are still marked by racial discrimination and socio-spatial exclusion. At the same time, their colonial city centres are recognised as UNESCO World Heritage, attracting thousands of tourists every year. In this ambivalent context, we focus on peri-urban neighbourhoods which tend to be ‘off the map’ of many tourists, researchers and political actors. In the face of violence and poverty, their dwellers are often stigmatised across-the-board as if they were morally inferior and incapable of fostering a peaceful social transformation. In contrast, we assume that their self-organised socio-cultural projects may not only (re)valorise Afro-descendant identities and life-worlds, but also change people’s strong evaluations of what is right and good, altering their visions of a good life. Presented by Prof. Dr. Rothfuß #geography #brazil #philosophy #postcolonialism #moralities #unibayreuth #universityofbayreuth